The impact of managerial ownership, institutional ownership, proportion of independent commissioner, and intellectual capital on financial distress - I Kadek Widhiadnyana; Ni Made Dwi Ratnadi (Journal of Economics, Business, and Accountancy Ventura, 2018)
Financial distress is a phase of the decline in the financial condition experienced by a company before the bankruptcy or liquidation occurs. One of the causes of financial distress is the company’s operating losses, caused its operating cash flow to be negative. During 2014-2016, there was 24 percent of manufacturing companies listed in Indonesia Stock Exchange (BEI) that has a negative pretax profit. The purpose of this study was to obtain empirical evidence of the effect of managerial ownership, institutional ownership, the proportion of independent commissioner board, and intellectual capital on financial distress. The population of this research is all of manufacturing companies listed on Indonesian Stock Exchange (IDX) on 2014-2016. The sample was taken using a non-probability sampling with a saturated sample technique. The numbers of samples analyzed were 423 financial reports of manufacturing companies published on IDX during 2014-2016. The analysis technique used in this research is multinomial logistic regression. It was found that managerial ownership has a negative effect on financial distress, institutional ownership has a negative effect on financial distress, proportion of independent commissioner has a positive effect on financial distress, and intellectual capital has a negative effect on financial distress.